Project Based Learning (PjBL) Model in the Pancasila Learning Profile of Fourth Grade Elementary School Students - Ni Luh Made Mita Oktaviani; I Made Citra Wibawa; Putu Nanci Riastini (Universitas Pendidikan Ganesha, 2023)
Most students have not been able to collaborate with friends and teachers. Apart from that, there are still many students who are not severe, and students cannot respect friends of different religions. This research aims to analyze the influence of the Project Based Learning (PjBL) learning model on the Pancasila student profile of fourth-grade elementary school students. This research is quasi-experimental with a nonequivalent posttest-only control group design. The population of this study was 149 fourth-grade elementary school students. Data collection methods use questionnaires and description tests. The research data were analyzed using descriptive and inferential statistical techniques (t-test). The results of data analysis showed that the average posttest score on the experimental group questionnaire was 67.44, which was in the very high category, and the average posttest score on the control group questionnaire was 46.04, which was in the medium class. Meanwhile, the average posttest score on the experimental group's description test was 76.2, which was in the very high category, while the average posttest score on the control group's description test was 52.31, which was in the medium class. The t-test analysis results show a significant influence of the Project Based Learning (PjBL) learning model on the Pancasila student profile of fourth-grade elementary school students. It was concluded that the Project Based Learning (PjBL) learning model could improve the shape of Pancasila students in fourth-grade elementary school students.